Assessment of Pharmacokinetic Interaction Between Gefapixant (MK‐7264), a P2X3 Receptor Antagonist, and the OATP1B1 Drug Transporter Substrate Pitavastatin. Issue 3 (24th November 2021) - McCrea, Jacqueline B.; Hussain, Azher; Ma, Bennett; Garrett, Graigory C.; Evers, Raymond; Laabs, John E.; Stoch, S. Aubrey; Iwamoto, Marian
Abstract: Gefapixant (MK‐7264, AF‐219), a first‐in‐class P2X3 antagonist, is being developed as oral treatment for refractory or unexplained chronic cough. Based on in vitro data, gefapixant exerts inhibitory activity on the organic anion transporter (OAT) P1B1 transporter. Therefore, a drug‐drug interaction study evaluating the potential effects of gefapixant on the OATP1B1 drug transporter, using pitavastatin as a sensitive probe substrate, was conducted. An open‐label, 2‐period, fixed‐sequence study in 20 healthy adults 18 to 55 years old was conducted. In period 1, a 1‐mg oral dose of pitavastatin was administered to each participant. After a ≥4‐day washout, in period 2 participants received a 45‐mg oral dose of gefapixant twice daily on days 1 through 4. On day 2 of period 2, pitavastatin was coadministered with the morning dose of gefapixant. Pitavastatin exposures following single‐dose administration with and without multiple doses of gefapixant were similar: geometric mean ratio (90% confidence interval) of pitavastatin area under the plasma concentration–time curve from time 0 to infinity (AUC0‐∞ ) (pitavastatin + gefapixant/pitavastatin alone) was 0.97 (0.93‐1.02). The ratio of pitavastatin lactone AUC0‐∞ to pitavastatin AUC0‐∞ was also comparable between treatments. Administration of gefapixant and pitavastatin was generally well tolerated, with no safety findings of concern. These results support that gefapixant has a low potential to inhibit the OATP1B1 transporter.